Occupations Shape Retirement across Countries - Philip Sauré; Arthur Seibold; Elizaveta Smorodenkova; Hosny Zoabi (Center for Economic Studies and ifo Institute (CESifo), 2023)
We study how occupations shape individual and aggregate retirement behavior. First, we document large differences in individual retirement ages across occupations in U.S. data. We then show that retirement behavior among European workers is strongly correlated with U.S. occupational retirement ages, indicating an inherent association between occupations and retirement that is present across institutional settings. Finally, we find that occupational composition is highly predictive of aggregate retirement behavior across 45 countries. Our findings suggest that events affecting occupational structure, such as skill-biased technological change or international trade, have consequences for aggregate retirement behavior and social security systems.
Keywords: E24; H55; J14; J24; J26; J82; 330; retirement; occupational distribution; cross-country analysis